(untitled) (Research, Society and Development, 2020)
Objective: Discuss from the literature aspects related to the control of the covid-19 pandemic in Brazilian territory and actions for the prevention and control of new events. Methods: An integrative review was carried out with the following guiding question: which actions to control the COVID-19 pandemic were highlighted in the Brazilian literature in 2020? ”. Results: 4 texts from the VHL and 20 from the academic Google were selected. The chronological distribution of the studies takes place especially after the month of April in the year 2020. Regarding the types of studies, 18 articles, 2 technical notes and 4 recommendations for pandemic control were selected. Discussion: The recurring themes were: Social isolation, use of PPE’s and hand hygiene; PHC contributions in this context and adaptations of care to address the population; and, finally, forms of prevention for workers stand out. The findings were categorized by systematic analysis as follows: Social isolation as the main initiative and other general measures; coping policies; and limitations and contributions of Primary Health Care and workers’ health. Conclusion: The texts are concatenated for the strategic solution of the problems arising from the pandemic and reflect legal and protocol mechanisms in the health field in view of the demands arising.